ЧОРИ БАХШИ УМИРОВ ИЖОДИГА БИР НАЗАР - Худайқулова, Л. (SCIENCE and SOCIETY, 2022)
This article discusses the image and motives in the epic "Sherali" from the repertoire of Chori Bakhshi Umirov.
Keywords: epic; bakhshi; image; motive; dynasty; emotional; heritage